O centro da cidade e o comércio: um estudo da importância das atividades terciárias na configuração espacial urbana de Uberaba - MG - Silveira, Leonardo José (2015)
The transformation of society, through time and space, along with changes in values and consumption patterns reverberate in the tertiary sector which is recreated and materialized in new concepts and customs. Based on this premise, this study offers a small contribution to public managers and urban planners, informing the dynamics of the tertiary sector, describing intrinsic elements and processes to commercial activities and retail services and its relationship with the city. Therefore, there was the search of comprehension of the tertiary sector\'s performance in the current spatial configuration of the center of Uberaba - MG, answering the following problem: how far the spatial configuration of the city center is influenced by the dynamics of trade and retail services? There are two options to consider: first, trade and retail services are promoters of structural transformations and second, they act passively responding to a given situation. It is believed that trade affects, as well as it is formatted by the spatial dynamics. This statement is discussed during the development this study. The research used investigative strategies and analysis divided into steps as methodological subdivision of four levels proposed by Libault (1971) comprising: data collection; analysis to correlate the theoretical information and field data collected; confrontation and correlation of information and, finally, conclusion. The results announce the importance of the tertiary sector as a producer agent, and landscape transformer, in a continuous and cyclical process of socio economic dynamics which form intra-urban centralities.